HARMONIZATION CONCEPT OF GOOD CORPORATE GOVERNANCE AND COMPANY CULTURE - Hudriyah Mundzir (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Implementation of principles for good corporate governance in a certain kind of company aims at managing and improving company’s performance. In fact, those principles of corporate governance has been, so far implemented less optimally. It is due to several drawbacks. The main problems in implementing good corporate governance principles is lack of sanction for companies which do not implement them and certain kind of culture encouraging people to obey more on informal regulation such as certain custom prevailing in certain community than on formal one. To overcome those problems of good corporate implementation, it is recommended that the state and its apparatus functioning as regulator should force companies to implement principles of good corporate governance and company culture as a unity of harmonious values followed by implementing rules of law and consistent law enforcement. Corporate world as market stakeholder implements good corporate governance as basic guidance of business and community holds social control objectively and responsibly.Keywords: company culture, harmonization, corporate governance